Jammu & Kashmir Eighth Five Year Plan (1992-97) & Annual Plan 1994-95 (Draft) - Planning Commission (Planning Commission, 1993)
A total investment of Rs.4000 crores is envisaged for the Eighth Five Year Plan (1992-97) including a component of about Rs.1800 crores as the spill over cost of continuing schemes. The Planning Commission adopted indicative posture leaving detailed sectoral profile to the States. Focus is on intensive investment in the area of industries, human resources development, creation of appropriate organizations and delivery system.
Planning and Development Department